Enhanced Sinterability, Thermal Conductivity and Dielectric Constant of Glass-Ceramics with PVA and BN Additions - Aribuga, Dilara; Akkasoglu, Ufuk; Cicek, Bugra; Balci-Cagiran, Ozge (MDPI, 2022)
With the rapid development of the microelectronics industry, many efforts have been made to improve glass-ceramics' sinterability, thermal conductivity, and dielectric properties, which are essential components of electronic materials. In this study, low-alkali borosilicate glass-ceramics with PVA addition and glass-BN composites were prepared and successfully sintered at 770 degrees C. The phase composition, density, microstructure, thermal conductivity, and dielectric constant were investigated. It was shown that PVA addition contributes to the densification process of glass-ceramics (~88% relative density, with closed/open pores in the microstructure) and improves the thermal conductivity of glass material from 1.489 to 2.453 W/K.m. On the other hand, increasing BN addition improves microstructures by decreasing porosities and thus increasing relative densities. A glass-12 wt. % BN composite sample exhibited almost full densification after sintering and presented apparent and open pores of 2.6 and 0.08%, respectively. A high thermal conductivity value of 3.955 W/K.m and a low dielectric constant of 3.00 (at 5 MHz) were observed in this material. Overall, the resulting glass-ceramic samples showed dielectric constants in the range of 2.40-4.43, providing a potential candidate for various electronic applications.
Keywords: glass-BN composites; PVA addition; low temperature sintering; microstructure; thermal conductivity; dielectric constant; LTCC; TEMPERATURE COFIRED CERAMICS; CRYSTALLIZATION KINETICS; FABRICATION; COMPOSITES; DESIGN; PHASE; B2O3; Chemistry; Materials Science; Metallurgy & Metallurgical Engineering; Physics